Herder og Grundtvig - sonderinger - Adamsen, Johannes (Grundtvig-studier, 2001)
Herder and Grundtvig By Johannes Adamsen The purpose of this paper is to reconsider various points in the writings of Grundtvig, and view them in their proper perspective by a reading of Johann Gottfried Herder (1744-1803). After a short presentation of Herder and his writings the article offers some thoughts on Grundtvig’s so-called .magel.se opdagelse. (unparalleled discovery) in order to show its systematic position in relation to the previous church history, and it points out that the problems leading to this discovery were to be found everywhere, and furthermore that Grundtvig’s solution was not all that unique. For instance the article considers the connection to the German theologian Franz Volkmar Reinhard.Subsequently, Grundtvig’s idea of history is examined in order to show that it is best understood in relation to Herder, if one takes into account that the Romantic movement came in between them as a sort of cultural shift. A definition of Romanticism is offered, and moreover it is postulated that Grundtvig’s understanding of the Bible in the light of the before-mentioned systematic problems can best be characterized as »poetical Biblicism«.Finally, it is argued that compared to Herder, Grundtvig finds different solutions to common problems, but that his solutions were inadequate as fas as the understanding of history is concerned, and barren as regards the systematic theological potential.